Layanan Kefarmasian Digital: Peluang Inovasi dan Tantangan Regulasi dalam Telemedisin dan E-Commerce Lintas Batas - Dewi, Rusmina Iswanti Kumala; Marshanda, Nanda; Sindy; Novansyah, Dwi Irnak (Pharmaceutical Journal, 2025)
The rapid development of digital technology has transformed various health and pharmaceutical sectors. Digital pharmacy refers to the use of information and communication technology to provide online pharmaceutical services such as consultations, therapy monitoring, and drug purchases through digital platforms, so as to improve access and efficiency of pharmaceutical services, especially in hard-to-reach areas. Cross-border telemedicine and e-commerce-based pharmaceutical services offer great opportunities, such as increasing access to pharmaceutical services in remote areas and accelerating drug distribution and can make it easier for patients to get drug information, consultations, and drug delivery without having to come directly to the pharmacy. However, the main challenges include regulatory and legal aspects, such as differences in regulations between countries that can hinder the operation of cross-border services. Limited access to technology and lack of public understanding of the use of digital platforms are also obstacles.